The new face of NASOM / Ahmad Aidil Abrisam Abdul Latiff - Abdul Latiff, Ahmad Aidil Abrisam (Faculty of Art and Design, 2020)
Most of the previous research focuses on having a good branding with creative logo. This research objective is to find a new face of the National Autism Society of Malaysia (NASOM).